AB1364-HPR PRELIMINARY CASE REPORT ON SHARING PATIENT HISTORY IN CLINICAL TREATMENT OF RHEUMATOID ARTHRITIS. (June 2019) - FUSAMA, MIE; Oliver, Susan; Nakahara, Hideko; Eijk-Hustings, Yvonne van; Kuroe, Yuriko
Abstract : Background: Rheumatoid arthritis (RA) is a chronic disease with periods of flare-ups and remissions, affecting daily life. Therefore, this disease requires lifelong management and support by the patients social circle and health professionals (HP). Objectives: The aim of this study was to follow up the history of patients with RA, and demonstrate an improved understanding at each point in their disease trajectory, whilst encouraging them to cope, and enabling HP to optimize support provided. Methods: We conducted two 30minute interviews with patients with RA. Interview questions included the patients perspective of their disease and disease information, effects on daily life, as well as psychological considerations using the Corbin and Strauss Chronic Illness Trajectory Framework approach [1]. This study was approved by the ethics committee of our hospital and informed consent was obtained. Results: The first case; An unmarried 68 year old female living alone. The patients mother also suffered from RA. The patient was vaguely aware of the hereditary nature of RA (pretrajectory phase) and did not result in a big shock to her and she accepted her the diagnosis relatively smoothly (trajectory onset phase). She was prescribed initially prescribed methotrexate but this proved infective and infliximab was commenced. Remission was achieved and at that time she was satisfied with her relationship with her primary physician (stable phase). Two years after beginning infliximab, she developed chest pain. However, her primary physician did not explore the problem and advised her that she had depression. She began to distrust him (unstable). She asked for infliximab to be stopped and requested her care be transferred to B university hospital where her mother was being treated. However, she was refused treatment due to the non-severity of her condition. She was unable to come to terms with refusal, and her physical and mental state deteriorated (downward phase). Her mother advised the patient to go to D hospital, where she was put on Etanercept achieving remission with no complications (comeback phase). At D Hospital; (1) her condition and the need for treatment were clearly explained to her, and she was able to actively participate in shared decision making; and (2) she was given access to support from Health Professionals (HP) such as nurses, who offered a patient centered approach listening to her concerns and advising her appropriately whilst offering general psychological support. A further 4 patients were interviewed. We will show the key phases of trajectories of their illnesses, the patients opinions about sharing their information with HP through interviewing, and the possibility of behavior change in the patients journeys. Conclusion: This study shows that a patient centered approach taking into account the stages of the illness trajectory benefits patients perceptions of their disease and ability to cope with their condition. It also highlights the importance of having the support of ones social circle, particularly at challenging times. Making a thorough record of the patients disease and QOL trajectory allows the patient to understand their disease process and associated life changes, and assist health professionals to provide the optimal support and resolve problems when they arise. This preliminary study focuses on understanding the value of different phases of the trajectory of illness and sheds more light on the relationship between patients and HP and how the disease process and patients perspectives of their disease can facilitate mutual trust and smooth future treatment. References: [1] Corbin JM. Sch Inq Nurs Pract 1998;12: 341. Disclosure of Interests: MIE FUSAMA: None declared, Susan Oliver: None declared, Hideko Nakahara: None declared, Yvonne van Eijk-Hustings Grant/research support from: UCB, Speakers bureau: Cellgene, Yuriko Kuroe: None declared